Effects of experiential learning on women’s participation in agricultural decision making in India - Meinzen-Dick, Ruth S.; ElDidi, Hagar; Falk, Thomas; Sanil, Richu (International Food Policy Research Institute, 2024)
Women’s decision-making in agriculture has received considerable research and policy attention in recent years. Decision-making is a key aspect of empowerment. For example, women’s input in productive decisions is a key indicator in the Women’s Empowerment in Agriculture Index (WEAI). Inclusion of women in decision-making can also help ensure that their knowledge and priorities are considered, which can lead to better agricultural outcomes and resource conditions. A cross-sectional study found that in Burkina Faso, India, Malawi, and Tanzania, households where women were more included in decision making on agricultural production produced more varied food-group crops with higher nutrient density. The question is how to strengthen women’s decision-making ability. A review of 12 agricultural development projects with explicit aims for women’s empowerment found that only 3 had a significant impact on women’s participation in agricultural and livelihood decision-making. An evidence scan on programmatic approaches to increasing women’s decision-making power found that the majority of such interventions focused on household- or community-level changes to social norms, technical training, or leadership, role models, and mentoring. The study notes the need for more contextualized studies of different programmatic approaches to increase women’s decision-making power and outcomes associated with the interventions.